The importance of learning Malay Sultanates in the context of the present federation of Malaysia - Wan Ahmad Fauzi, Wan Husain; Intan Maizura, Abd Rashid; Najuwa, Mohd Nasir; OD., M. Anwar; Irza Hanie, Abu Samah (Psychology and Education Journal, 2021)
This paper views the emergence of the present Malay Sultanates from the historical perspective. Furthermore, as it is one of the important elements in Malaysian history, a close study of the Malay Sultanates would enhance interest in Malay history and promote unity among Malaysian citizens. It is based on the Malay classical literary texts of Sejarah Melayu, Hikayat Johor Serta Pahang and Peringatan Salasilah dari Raja-Raja Johor hingga ke Riau Lingga, Singapura, Pahang dan Terengganu. It is also based on ancient foreign texts such as those by Alfonso De Albuquerque (1512) and Tome Pires (1512), both Portuguese.